Analisis Kelayakan Usaha Kelapa Muda Jelly Pada PT.Taya Mandiri Indonesia - Muhira Muhira; Sri Fitri; Ainal Mardhiah; Sarini Sri Utari (Departemen Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala associated with AAI (Asosiasi Agribisnis Indonesia). Jl. Tgk. Hasan Krueng Kalee No. 3, Kopelma Darussalam, Banda Aceh, 23111, Indonesia. Email: agrisep@usk.ac.id, 2026)
Young coconut is a commodity with high economic value and considerable potential for processing into various value-added products,one of which is coconut jelly. This innovation provides added value while expanding market opportunities for processed coconut products. Based on the results of a preliminary obsevation, PT. Taya Mandiri Indonesia was selected as the research location because it is one of the producers that has been actively producing young cococnut jelly in Banda Aceh city. This study aims to analyze the business feasibility of the Coconut Jelly enterprise at PT. Taya Mandiri Indonesia. This study employed a case study approach. The sample was selected using a purposive sampling technique, with PT. Taya Mandiri Indonesia serving as the research subject. The data used consisted of primary data obtained through interviews and direct observation, as well as secondary data collected from relevant institutions. The feasibility analysis was conducted by calculating production costs, revenue, income, and the Revenue Cost Ratio (R/C Ratio). The results showed that the total production cost of the Coconut Jelly business was IDR 2.68.337 per day, with total revenue of IDR 3.200.000 per day. The net income earned was IDR 519.663 per day, and the R/C Ratio value was 1,19. This value indicates that every IDR 1 spent generates IDR 1,19 in revenue. Based on the feasibility criteria (R/C Ratio > 1), the business is considered feasible to operate and further develop. The conclusion of this study is that the Coconut Jelly business has good potential for further development, especially through expanding marketing networks, utilizing digital-based supply chain technology, and managing raw material supplies sustainably to ensure production continuity.